Jump and other stories - Gordimer, Nadine (London : Bloomsbury publishing, 2003)
"Fifteen thematically and geographically wide-ranging stories from t he Nobel Prize winner, with settings ranging from suburban London to Mo zambique"--
Jump -- Once upon a time -- The ultimate safari -- A find -- My fath er leaves home -- Some are born to sweet delight -- Comrades -- Teraloy na -- The moment before the gun went off -- Home -- A journey -- Spoils -- Safe houses -- What were you dreaming? -- Keeping fit -- Amnesty.
Keywords: Apartheid -- South Africa -- Fiction; South Africa -- Social conditions -- 1961-1994 -- Fiction